ANTIBACTERIAL POTENCY OF CELL FREE SUPERNATANT PRODUCED BY LACTIC ACID BACTERIA ISOLATED FROM INDONESIAN FERMENTED FISH PRODUCTS AGAINST HISTAMINE-PRODUCING BACTERIA - Masagus Muhammad Prima Putra; Muhammad Yaafi Al-Hammam; Giffarri Ahsan; Klara Kharisma Bunga Chandra; Indun Dewi Puspita (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2022)
The toxicity caused by high histamine content produced by histamine-producing bacteria (HPB) during the fermentation of scombridae fish group based fermented fish products is still a problem that requires a solution. This study aims to explore the potential of secondary metabolites in the form of cell free supernatant (CFS) produced by lactic acid bacteria (LAB) as antibacterial agents against HPB. The LAB was isolated from the fermented fishery products named bekasan, cincalok and fish sauce using MRS-Agar and fermented on MRS-broth for 48 hours. CFS was collected by centrifugation at 15,000 x g for 15 minutes, followed by heating at 100oC for 3 minutes and pH neutralization with 0.1N NaOH. Antimicrobial activity of CFS then tested on HFB namely Morganella morganii TK7, Citrobacter freundii CK1, and Klebsiella sp. CK13.2 (collection of the Laboratory of Fisheries Product Quality and Safety, Department of Fisheries UGM) using the macrodilution method. Isolation of LAB from all three products successfully isolated 34 isolates. The results of the antibacterial activity showed that 4 isolates namely GMCN 1.12, GMBK 2.6, GMBK 2.7, dan GMKI 2.1 were able to inhibit HFB growth more than 70%. The highest activity was shown by GMBK 2.7 which inhibits 98% against Morganella morganii TK7, 99% against Citrobacter freundii CK1, and 84% against Klebsiella sp. CK13.2. The antimicrobial activity was reduced after proteolytic enzymes were added suggesting that the bioactive compound came from peptide-based substances like bacteriocin.